Hubungan Involusi Sel-sel Sekretoris Kelenjar Ambing dengan Produksi Susu Domba Priangan dengan Dua Level Pakan - Adriani, Adriani (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2009)
Forty-two    lactating  Priangan  ewes  receiving  two  levels  of  ration  were  used  to  study  the  relationship  between  rate  of  mammary  gland  involution  and  milk  yield.  The  experimental  ewes  were divided  into  two  groups.  One  group  received  basal  ration  (I  =  12%  CP,  65%  TDN)  and  the  other received improved ration (II  = 15% CP, 75% TDN) during lactation.  Twelve  ewes were sacrificed on the  parturition  to  determine  mammary  gland  growth  at  the  beginning  of  lactation.  The  other  twenty-seven  were  maintained  for    3  months  of  lactating  to  determine  milk  yield  and  mammary  gland  indices (dry-fat free tissue and collagen) at the end of lactation. The results of the experiment indicated that ewes with higher milk production had  greater mammary gland involution. Ewes with higher mammary gland  indices  either at the   beginning or at the end of lactation  had higher milk production.  Improve  ration  decreased mammary gland involution.